Kinetic study on the reaction of p‐tert‐butylbenzoic acid with methanol catalyzed by deep eutectic solvent based on choline chloride. Issue 12 (7th August 2021) - Guo, Yuan; Tang, Linmao; Xue, Weilan; Zeng, Zuoxiang
Abstract: The synthesis of methyl p ‐tert‐butylbenzoate using deep eutectic solvent (DES) as a green catalyst was studied in this work. Four DESs were prepared by combining choline chloride (ChCl) and p ‐toluenesulfonic acid monohydrate (PTSA) with different molar ratios (1:1–3). It was found that ChCl‐1.5PTSA with a molar ratio of 1:1.5 was superior to other DESs both in physical properties and catalytic performance. Therefore, it was selected to carry out the kinetic experiments. The effects of stirring speed, temperature, molar ratio of methanol to p ‐tert‐butylbenzoic acid, and catalyst loading on the conversion of p ‐tert‐butylbenzoic acid were discussed. In addition, the reaction kinetics of p ‐tert‐butylbenzoic acid and methanol with ChCl‐1.5PTSA as catalyst was explored in the temperature range of 332.15–349.15 K, and the experimental data were well fitted by pseudo‐homogeneous model. Moreover, the recyclability of ChCl‐1.5PTSA was evaluated. The result shows that the catalyst could be easily separated from the reaction system without any extractant, and the performance of the catalyst remains stable in multiple times recycling. Therefore, ChCl‐1.5PTSA is expected to be an efficient and environmentally friendly catalyst for the methyl esterification of p ‐tert‐butylbenzoic acid with a bright future in industrial application.